Study of the Effect of Radiology X-ray and its Risks on Human - Manal Dakhil Sakhil (Scientific Trends, 2022)
In this research, we must know the dangers of x-rays on the human body were identified. The possibility of damage that radiation can cause is related to being in high quantities, while radiological examinations are governed by international controls and standards that determine the amount of radiation within safe limits. The possibility of damage due to an examination using x-rays is a very small theoretical possibility. It is known that X-rays are a form of energy (electromagnetic waves) such as light and radio waves. But the difference is that the rays have the ability to penetrate the human body unlike light. After the discovery of X-rays by the scientist Roentgen, it was exploited in the medical field for the purpose of viewing and diagnosing the internal organs in the human body. We can say that the use of radiology in the medical field has a great impact in helping doctors to make decisions in treating their patients better.